Contextualizing Procurement Maturity: Lessons from Government Procurement for Enhancing Regional-Owned Enterprise (BUMD) Performance - Sutisna, Nandang; Rahman, Titik Khawa Abdul; Bin Mansor, Shazali (International Journal of Multidisciplinary Approach Research and Science, 2025)
Procurement governance represents a strategic function critical to the success of public organizations, particularly Regional-Owned Enterprises (BUMDs), which operate under hybrid mandates combining public service delivery and market competitiveness. This study critically examines the applicability of the Indonesia Procurement Maturity Model (IPM2) to BUMDs and proposes an adapted conceptual framework better suited to their unique governance complexities. Through analytical deconstruction, the study finds that while elements such as transparency, accountability, and technology utilization in IPM2 are directly adoptable, significant adjustments are necessary in organizational structures, competency frameworks, and risk management approaches. Rigid elements tied to governmental budget cycles and inspectorate-driven oversight are deemed incompatible with BUMD operational realities. An adapted maturity model is proposed, positioning procurement as a strategic enabler supported by five interconnected adaptive dimensions: Strategic Human Capital Development, Agile Institutional Structures, Performance-Driven Management Systems, Strategic Technological Integration, and Proactive Risk and Opportunity Management. Grounded in contingency theory and contemporary hybrid governance literature, the model reframes procurement maturity as a dynamic, value-driven system rather than a linear, compliance-oriented progression. This research offers both a practical roadmap for BUMDs and a conceptual contribution to the evolving field of procurement governance in hybrid public organizations.